2016
DOI: 10.1007/978-3-319-22536-4_22
|View full text |Cite
|
Sign up to set email alerts
|

Sonodynamic Therapy: Concept, Mechanism and Application to Cancer Treatment

Abstract: Sonodynamic therapy (SDT) represents an emerging approach that offers the possibility of non-invasively eradicating solid tumors in a site-directed manner. It involves the sensitization of target tissues with a non-toxic sensitizing chemical agent and subsequent exposure of the sensitized tissues to relatively low-intensity ultrasound. Essentially, both aspects (the sensitization and ultrasound exposure) are harmless, and cytotoxic events occur when both are combined. Due to the significant depth that ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
173
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(177 citation statements)
references
References 82 publications
1
173
0
3
Order By: Relevance
“…It is now clear that when exposed to ultrasound, the porphyrin-based sensitizers generate ROS, causing cytotoxicity [40]. Consistent with this finding, we found that ALA-SDT increased the intracellular ROS levels in Jurkat cells (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…It is now clear that when exposed to ultrasound, the porphyrin-based sensitizers generate ROS, causing cytotoxicity [40]. Consistent with this finding, we found that ALA-SDT increased the intracellular ROS levels in Jurkat cells (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…An example of an alternative tumor eradication method is SDT. This therapy is based on a synergistic effect on a cancer cell by sonosensitizer and US [199]. US can activate particles of compounds called sonosensitizers.…”
Section: Reviewmentioning
confidence: 99%
“…In comparison with UV or NIR radiation, US penetrates tissues much more effectively as it reaches deeper depths tumor cells. The introduction of sonosensitizers into cancer cells and their subsequent exposure to US in order to generate ROS is the underlying factor of SDT [199, 200] (Fig. 2).…”
Section: Reviewmentioning
confidence: 99%
“…Compared with the light used in PDT, ultrasound has better penetrability, which can easily act on the lesion at a deep site. 11,12 Besides, it is currently believed that the combination of PDT and sonodynamic therapy (SDT) may decrease the sensitizer dosage and ultrasound/ light energy, which can further reduce the side effects, while enhancing the curative effect dramatically. [13][14][15][16][17] Thus, PDT combined with SDT (PSDT) is considered for the lesion of deep site in the present study.…”
mentioning
confidence: 99%